Perforators as recipients for free flap reconstruction of the inguinal and perineal region. Issue 8 (13th October 2015) - Seo, Bommie F.; Yun Choi, Jong; Ho Han, Hyun; Young Oh, Deuk; Won Rhie, Jong; Tae Ahn, Sang; Moon, Suk‐Ho
Abstract : Objective: Extensive defects of the perineal or inguinal area require well vascularized free flap coverage. This area has an abundance of perforating arteries and veins based on vessels from the femoral artery and internal iliac artery. We present our experience on the use of perforators as recipient vessels in reconstructing soft tissue defects of the perineal and inguinal area with free flaps. Patients and Methods: From March 2012 to August 2014, 13 patients underwent free flap reconstruction for soft tissue defects of the inguinal or perineal area. Perforating arteries with diameters ranging from 0.7 to 1.2 mm were used as recipient arteries. Accompanying veins or neighboring superficial veins were secured as recipient veins. Results: All flaps survived attached to a recipient perforator with a diameter ranging from 0.7 to 1.2 mm. These vessels were found in the inguinal or perineal areas, regions that are supplied by the superficial circumflex iliac vessels, superficial inferior epigastric vessels, superficial and deep external pudendal vessels, lateral and medial circumflex femoral vessels, and internal pudendal vessels. There were no cases of arterial insufficiency or venous congestion, flap necrosis, or infection. A single case of hematoma beneath the flap was treated by simple evacuation. There were no donor complications. Conclusion: Using perforators as the recipient during free flap reconstruction of the inguinal and perinea area allows the surgeon to choose from a wider choice of vessels, and yields acceptable flap survival. © 2015 Wiley Periodicals, Inc. Microsurgery 35:627–633, 2015.